Micro- and nano-scale fluid flow and heat transfer with phase change in a channel - Sun, Qiangqiang (2021)
Micro/ Nanoscale fluid flow and heat transfer with phase change in a channel widely exist in film cooling of aircrafts and electronic devices, etc. Compared with their macroscale counterpart, Micro/ Nano-scale fluid flow and heat transfer show some new features such as velocity slip, temperature jump, density layering and non-uniform viscosity phenomena. Besides, some factors (i.e., axial conduction, viscous dissipation and rarefied effect) that are normally neglected in macroscale flow and heat transfer become dominant at Micro/ Nano-scale counterparts. In this thesis, Micro/ Nanoscale fluid flow and heat transfer are thoroughly investigated by various approaches. The two-dimensional energy equation with a first-order velocity slip model and a temperature jump model is solved analytically, and impacts of viscous dissipation, axial conduction and rarefied effect on the local Nusselt number, the asymptotic Nusselt number and the bulk temperature profile of fluid are clarified. The second law analysis method based on the local entropy generation rate is then proposed to compute and visualize the resistance of flow at low Reynolds number featuring velocity slip after implementing the linear Navier velocity slip boundary condition in OpenFOAM through three schemes. Then, classical molecular dynamics simulations are performed to reveal the features of Micro/ Nanoscale flow and heat transfer (i.e., velocity and temperature slip, non-uniform density and viscosity profiles). This study is followed by the study of the phase change (i.e., thermal de-icing and the icephobic coatings) at the molecular level.